Model Bisnis Baru Dan Adaptasi Lembaga Dakwah di Era Disruptif - Kendy, Muhammad; Castrawijaya, Cecep (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2025)
The disruptive era triggered by the development of digital technology, changes in social behavior, and the increasing flow of global information has fundamentally changed the da'wah ecosystem in Indonesia and the Islamic world in general. Digital transformation has not only shifted religious communication media to digital platforms but also introduced new logic in the production, distribution, and consumption of da'wah content. Da'wah institutions that previously relied on face-to-face approaches and hierarchical organizational structures are now required to adopt new business models that are more flexible, participatory, and oriented towards sustainability. This article examines the concept of a digital da'wah business model in depth through an analysis of value innovation, monetization mechanisms, congregation engagement strategies, and the formation of a collaborative ecosystem between da'wah institutions, technology platforms, and digital communities. Furthermore, this article explores how da'wah institutions can respond to disruptive challenges through organizational digital transformation, improving the digital competence of da'i (preachers), and developing financing schemes relevant to the development of Sharia-based digital philanthropy. A literature review shows that platform-based digital da'wah can expand the reach of da'wah, strengthen interactions with congregations, and improve program sustainability. However, it also poses risks related to the commercialization of da'wah, the degradation of religious authority, and the amplification of algorithmically biased religious narratives. Therefore, new business models for da'wah institutions must be strategically designed to integrate da'wah values, institutional sustainability, and digital ethics to survive and thrive in an ever-evolving disruptive environment.